Circular Economy and the Tourism Industry - Costa, Berta José Fernandes (2020)
The tourism industry has been growing at a remarkable rate and emerging as one of the major social and economic industries, and consequently one that boosts economic development that mostly supports countries’ gross domestic product (GDP). At the same time, it stands out as an industry which activities generate a considerable negative impact on the environment as it is configured according to the linear model of production and consumption, in which products are disposed of after usage, causing massive waste. From this standpoint, circular economy (CE) materializes as a new strategy, as it balances economic progress with the sustainable use of natural resources.In this regard, the purpose of this research document is to outline the conceptual dimension of CE and its principles, and propose a conceptual model which may allow the tourism sector to transform itself into a more sustainable industry and one which may succeed in generating multidisciplinary benefits and in parallel mitigate environmental, social and economic constrains. For this purpose, a literature review was carried out, as a means to highlight the tourism industry as one of the sectors which may contribute significantly and positively to the implementation of the long expected circular economy, where stock value is maintained in economy for the longest period of time.